Walimah atau Pesta Perkawinan sebagai Praktik Sunnah dalam Perspektif Hukum Islam - Meifiani Ritonga; Muhammad Amar Adly (KAMPUS AKADEMIK PUBLISING, 2026)
Walimah or wedding celebrations are one of the sunnah practices in Islam that have religious and social dimensions. However, in contemporary society, their meaning has often shifted to become an event of prestige and a symbol of social status. This shift has the potential to cause waste and economic burdens that are not in line with the principles of Islamic law. This study aims to examine the position of walimah from the perspective of Islamic law and analyze the principles and practices of its implementation in modern society. The research method used is a qualitative approach with library research, with data sources in the form of the Qur'an, Hadith, classical fiqh books, and relevant contemporary scientific literature. Data analysis was conducted descriptively and analytically using a normative-juridical approach. The results of the study show that walimah is considered a highly recommended sunnah mu'akkadah, with the main principles of implementation being simplicity, affordability, and benefit, as well as the prohibition of extravagance (israf and tabzir) However, the practice of walimah in society often deviates from this principle due to the influence of customs and social pressure. This study concludes that the implementation of walimah can accept elements of local customs and culture as long as they do not conflict with Sharia values, so that walimah should ideally be returned to its essence as a means of gratitude, announcement of marriage, and strengthening of social solidarity.